Snack food consumption among Bangladeshi children, supplementary data from a large RCT - Kaniz Jannat; Stephen P. Luby; Leanne Unicomb; Mahbubur Rahman; Peter J. Winch; Md. Iqbal Hossain; Christine P. Stewart (Wiley, 2020)
Abstract Childhood obesity has been associated with consumption of energy‐dense foods such as caloric beverages and fast foods. Many low‐ and middle‐income countries like Bangladesh are now experiencing a rising problem of noncommunicable diseases along with the long‐standing problem of stunting and undernutrition. WASH Benefits Bangladesh was a large community‐based cluster randomized controlled trial conducted in rural Bangladesh. Study clusters were randomized into seven arms: single nutrition (N); water (W); sanitation (S); hygiene (H); combined water, sanitation, and hygiene (WSH); WSH and nutrition (N + WSH); and a double sized control (C). Nutrition intervention messages included four promotional components: maternal nutrition, breastfeeding, complementary feeding, and lipid‐based nutrient supplements. The World Health Organization infant food frequency questionnaire (24‐hr recall and 7‐day recall) was administered at Year 1 and Year 2 of intervention. The likelihood of any snack food consumption was significantly lower (odds ratio 0.37: 95% confidence interval [0.28, 0.49]) in the nutrition intervention arms compared to the control arm in Year 2 follow‐up. In addition, in the water intervention arm, fewer children (about 50% less) consumed soft drinks, but not the other sugar‐sweetened beverages, compared with control in Year 2. There were no other differences between groups. Simple messages about balanced diet and feeding family foods were effective in lowering commercially produced snack food consumption of the young children in low‐income rural communities of Bangladesh. Provision of safe water apparently encouraged mothers to reduce offering unhealthy beverages to the young children.